The influence of the volatiles on the slag composition for the heating process - Zhao Z.-Y.; Zhao J.-X.; Cui Y.; Lu L.; Wang G.-H. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The physicochemical properties of slag are of great importance in pyrometallurgy. If there is a volatile component in the slag, evaporation will inevitably occur. As a result, the slag composition will change, and the measured results will be inconsistent with the original slag composition. Therefore, the traditional methods can be applied to determine the properties of slag, however, the change in slag composition will lead to the inaccuracy of the results. Two typical kinds of slag ESR slag with higher CaF2 and Pb smelting reduction slag with higher PbO were chosen, and melting point measurements were taken as an example to demonstrate the new method in practice. Weight loss measurements and evaporation test with thermogravimetric (TG) analysis, as well as high-temperature mass spectrometer (MS) tests were carried out to identify the volatiles. It was found that CaF2 and MgF2 is the main volatiles with a small amount of AlF3 to ESR slag and PbO is the main volatile with a small amount of ZnO. Based on these points and the weight loss, the slag melting points measured with traditional method and the slag chemical composition were modified to fit the melting point value. This way is proved to be feasible in theory and practice. Some suggestion for further research are proposed. The work will be of significance for both slag and molten salt with volatiles.